Application of nanotechnology in food: processing, preservation, packaging and safety assessment. Issue 11 (November 2022) - Biswas, Rahul; Alam, Mahabub; Sarkar, Animesh; Haque, Md Ismail; Hasan, Md. Moinul; Hoque, Mominul
Abstract: Even though nanotechnology is extensively applied in agriculture, biochemistry, medicine and many other sectors, it is a developing field that conforms to new and more complex applications in food systems as compared to other technologies. It offers a viable strategy for integrating cutting-edge technology into a wide range of operations related to the production, development, fabrication, packaging, storage and distribution of food. The most fundamentally sophisticated technology in nano-based food science, nanoparticles deal with a wide range of nanostructured materials and nano methods, including nanofood, nanotubes, nanocomposites, nano packaging, nanocapsules, nanosensors, liposomes, nanoemulsions, polymeric nanoparticles and nanoencapsulation. This method is developed to increase food solubility and shelf life, availability of bioactive chemical, the protection of food constituents, nutritional supplementation, fortification and food or constituent delivery. Additionally, it serves as an antibacterial agent by generating reactive oxygen species (ROS) which cause bacterial DNA damage, protein denaturation and cell damage. Although the use of nanotechnology in food applications is advancing, there are certain negative or dangerous effects on health related to the toxicity and dangers of ingesting nanoparticles in food. The use of nanotechnology in the food industry, notably in processing, preservation and packaging, with its promising future, was addressed in this study. The toxicity of nanoparticles in food as well as its development in food safety assessments with certain areas of concern were also reviewed. Abstract : Nanotechnology; Processing; Preservation; Packaging; Safety assessment.